Interpretation of Ibrahim's Wife Laughter in Al-Qur'an Story From The Gabriel Said Reynolds Perspective - Arrois, Syaiful Makhi Ula; Yunus, Nur Rohim (Universitas Islam Tribakti Lirboyo Kediri, 2023)
The story of Prophet Ibrahim is one of the most frequently told stories in the Qur'an. This article aims to analyze Gabriel Said Reynolds' interpretation that highlights the aspect of Prophet Ibrahim's wife's laughter found in the Qur'an. This study uses a qualitative approach to the literature review type. This study found that1) Reynolds shows that the laughter of Prophet Abraham's wife, Siti Sarah, can be understood in two ways: as an expression of joy or astonishment. From Reynolds’s perspective, laughter also shows Sarah's disbelief in the good news delivered by the angels. Reynolds offers an interpretation that differs from the perspectives of most Islamic scholars. Reynolds is a linguist and historian of Christianity, so he provides an outsider's view of the Qur'ān. Nevertheless, Reynolds’s interpretation still provides an interesting insight into the story of Prophet Abraham and how interpretations can vary depending on the perspective used. 2) The story of Prophet Abraham shows the importance of trust in and loyalty to God. However, through Reynolds’s interpretation, we can also understand that trust itself can sometimes be questioned and understood in different ways. In this case, the laughter of Prophet Ibrahim's wife reminds us that trust in God can be expressed in many ways, including through expressions of joy or disbelief. Contribution: This study enriches Qur'anic interpretation by showing that Sarah's laughter has diverse meanings based on linguistic and historical perspectives.